The Impact of Personal and Professional Experiences: Holistic Exploration of Teacher Identity - Bukor, Emese (Working Papers in Language Pedagogy, 2013)
This paper investigates the impact of personal and professional experiences on the development of teacher identity. The holistic perspective in this article refers to the language teachers’ exploration of their personal and professional experiences with the use of both conscious/rational and intuitive/tacit thought processes. Three language teachers who participated in this study explored the beliefs, perceptions, and interpretations originating in their personal, educational, and professional experiences which also affected their teacher identity. Reflexive autobiographical journaling, a guided visualization activity, and three in-depth interviews were used in the research methodology. The results confirm that teacher identity is deeply embedded in one’s personal biography. The participants’ beliefs and interpretations rooted in their family environment influenced their early school experiences, career choice, instructional practice, teaching philosophy, and teacher identity. The results suggest that the analysis of teachers’ personal life experiences and their influence on professional practice can lead to a holistic understanding of the dominant influences on the development of teacher identity. The implications of this research are that a broader spectrum of the influences on teacher identity development needs more overt attention in professional development. This paper argues for the necessity of designing an integrated personal and professional development program for language teachers.